Effect of a sustained-release formulation of β-alanine on laboratory parameters and paresthesia in recreational trained men: a randomized double-blind placebo-controlled study - Maestre-Hernández, Ana Belén; Pérez-Piñero, Silvia; López-Román, Francisco Javier; Andreu-Caravaca, Luis; Luque-Rubia, Antonio J.; Ramos-Campo, Domingo J.; Díaz-Silvestre, María José; Ávila-Gandía, Vicente (Frontiers in Nutrition, 2023)
Introduction: Beta-alanine is a non-essential amino acid that has been a focus of increasing research by its role as ergogenic aid to improve muscle performance.A randomized, double-blind and controlled trial was conducted to determine the effect of a nutritional supplement of a sustained-release formulation of β-alanine in recreational trained men. The active product was an innovative sustained-release β-alanine microgranules powder blend, administered at high doses (15 g/day) divided into 3 intakes during 30 days. There were 10 participants in the experimental group and 9 in the placebo group, with a mean age of 22.5 ± 3.3 years. Participants were testing at baseline and at the end of study.In the β-alanine group, there were statistically increases in serum triglycerides, LDLcholesterol, and urea nitrogen at the end of the study as compared with baseline, although there were no differences with the control group. The occurrence of paresthesia, described above all as tickling, was the majority but presented VAS score less than 3/10 in almost all subjects.Discussion: More studies are required to evaluate the changes in blood parameters that can be caused by high intake of β-alanine during a long period of time.The study was registered in the ClinicalTrials.gov (NCT05334121).